Edith : the rogue Rockefeller McCormick - Ross, Andrea Friederici, 1965- (Carbondale : Southern Illinois University Press, 2020)
"Daughter of the oil titan and wife of the the son of the Reaper King, Edith Rockefeller McCormick was a woman wronged, left to fend for herself in the face of bankruptcy and cancer."--
Rockefeller Family Tree -- McCormick Family Tree -- Growing Up Rockefeller, 1872-88 -- The Prince of McCormick Reaper, 1888-95 -- Trickle Down Edith, 1896-99 -- The Show Must Go On, 1900-1904 -- Dangers, 1905-10 -- Grand Causes, 1909-11 -- Trying to Stay Sane, 1911-13 -- A New Father Figure, 1913-14 -- In for the Long Haul, 1915-16 -- Psychological Club, 1916-17 -- A Family in Tatters, 1917-20 -- Trying to Find a Way Home, 1919-21 -- On Her Own, 1921-22 -- A Year in the Life, 1922-23 -- Partnership, 1921-25 -- Elder Stateswoman, 1925-28 -- Full Steam Ahead, Blindly, 1926-28 -- Disaster, 1928-32 -- Death, 1932 -- Aftermath, 1932 -- Legacy.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 16, 2020).
Master record variable field(s) change: 050
Keywords: McCormick, Edith Rockefeller, -- 1872-1932.; McCormick, Harold F. -- 1872-1941.; McCormick family -- Art patronage; Rockefeller family; McCormick, Edith Rockefeller, -- 1872-1932.; McCormick family; McCormick, Harold F. -- 1872-1941.; Rockefeller family; Art patrons -- United States -- Biography; Socialites -- Illinois -- Chicago -- Biography; Philanthropists -- United States -- Biography; Chicago (Ill.) -- Social life and customs -- 20th century; Art patronage; Art patrons; Manners and customs; Philanthropists; Socialites; Illinois -- Chicago; United States; 1900-1999; Electronic books; Biographies